Value-in-use in a B2B food service logistic context - Luís Miguel de Castro Ferreira; João Menezes (Tourism & Management Studies)
The main objective of this research is to understand the way a provider participates and contributes in the value co-creation process and identify the drivers that contribute to it. Given the nature of the phenomena under study a qualitative research approach was chosen to conduct this study. To reach a deep understanding about the phenomena in the B2B empirical context where it takes place, a case study was conducted and data was collected through semi-structured interviews to key informants involved in the process. A link between value-in-use dimensions emerged suggesting the importance to the logistic provider to adapt its operation and internal organization in order to better contribute to the value creation process. The mechanisms that influence the experience lived by the logistic provider’s customer were identified and point to the importance of interactions and building a strong relationship in order to create a trust and collaborative environment between companies.